Pentingnya Manajemen Dalam Berwirausaha - Telaumbanua, Yana Sarah; Halawa, Sahabat (CV. SINAR HOWUHOWU, 2026)
Management is a fundamental determinant of entrepreneurial success and sustainability, particularly in micro-enterprises. Many businesses with promising products and market opportunities fail to grow due to weak managerial practices rather than a lack of capital or innovation. This study aims to examine the importance of management in entrepreneurial activities by analyzing the implementation of core management functions planning, organizing, actuating, and controlling at Fotocopy Delaux Paper, a micro-enterprise located in Gunungsitoli, Indonesia. A qualitative descriptive approach was employed to capture an in-depth understanding of managerial practices as they occur in real business settings. The research subjects consisted of the business founder and employees, selected through purposive sampling. Data were collected through semi-structured in-depth interviews, direct observation, and document analysis, and were analyzed using interactive qualitative techniques involving data reduction, data display, and conclusion drawing. Data credibility was ensured through source and technique triangulation. The findings indicate that planning is the most prominent management function and plays a crucial role in maintaining business continuity, although it is implemented in an informal, undocumented, and short-term oriented manner. Organizing emerged as the weakest function, characterized by unclear task distribution and role overlap, resulting in reduced operational efficiency. Business implementation is strongly influenced by the founder’s leadership, which is participatory and role-model–oriented but also creates a high dependency on the owner. Furthermore, controlling and performance evaluation are conducted irregularly and reactively, limiting their effectiveness in supporting strategic decision-making. This study highlights that even simple but consistently applied management practices significantly contribute to the performance and sustainability of micro-enterprises.